UPAYA MENINGKATKAN HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK MELALUI MEDIA RINTANGAN PADA SISWA KELAS X SMAN 1 GUNUNG SARI - Febrianto, Luqi; Subagio, Subagio; Lubis, Ridwan (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
Abstract: Background in this study the factors that influence learning outcomes are not realized by the physical education teacher of SMAN 1 Gunungsari, appearing in the learning field is only done conventionally, which results in long jump learning outcomes of students whose percentage of incompleteness is greater than percentage of students completeness. Sehinnga researchers interested in carrying out research with the title of efforts to improve the learning outcomes of long jump squat style through media obstacles in class X students of SMAN 1 Gunungsari in the 2018/2019 academic year. class x SMAN 1 Gunusngsari Academic year 2018/2019 through learning with media obstacles. The method used in this study is the method of observation, testing, and documentation. The results of the analysis of researchers’ data with statistics obtained the initial condition value with an average of 61.5 or by 28% then in the first cycle the condition experienced an increase in the average value of 70.4 or 59% completion but this increase still has not reached the target set before it, the next cycle is continued with an average score of 81.3 or a percentage of completeness of 87.5%. If the target has been reached, the learning process activities stopped in the second cycle. Based on the results of research and discussion, it can be concluded that Physical Education learning with long jump material through the medium of obstacles can improve long jump skills of class X students of SMAN 1 Gunung Sari in the academic year 2018/2019. The percentage of students who reach the Minimum Mastery Criteria (KKM) is more than 80%, which is 87.5%